Analisa Kualitas Layanan Website Elearning MyBEST UBSI Menggunakan SERVQUAL. - Nurfia Oktaviani Syamsiah; Sumanto; Hariyanto; Indah Purwandani (PUSAT SAINS INDONESIA, 2021)
Higher education is an institution that is expected to produce quality human resources in order to compete in the global market. To produce quality human resources, quality services are needed in accordance with the needs of the industrial world in general. The SERVQUAL method basically can be used in various service sectors including the education sector. Gap score analysis on SERVQUAL will assist educational institutions in assessing the quality of services provided and identify which dimensions require improvement or improvement of service quality. The purpose of this study is to analyze the service quality of the MyBest UBSI e-learning website and find out the service quality indicators that are a priority to be improved using the SERVQUAL method. The five dimensions of SERVQUAL are tangibles (direct evidence), reliability (reliability), responsiveness (responsiveness), assurance ( assurance) and empathy (empathy) are translated in the form of questions asked through an online questionnaire. From the test results using the SERVQUAL method, it can be seen that there is a gap between user expectations and perceptions, the variable that is most considered satisfactory is the responsive variable and the variable with the lowest level of satisfaction is the assurance variable.